Market arrangements used by small scale bean farmers in Kenya: What needs to change for sustainable trade volumes? - Wanjala, S.P.O; Karanja, D.; Wambua, S.; Otiep, G.; Odhiambo, C.; Birachi, Eliud Abucheli (African Journals Online, 2019)
Markets and marketing of common beans (Phaseolus vulgaris L.) is a major issue of concern to small scale farmers and other actors in the bean value chain in Kenya, particularly inconsistency in supplying sufficient volumes required for trade. This case study assessed market arrangements used by small scale farmers in the Lake Basin and Lower Eastern bean corridors of Kenya, to determine which markets work for rural producers and what changes are needed to produce and supply sufficient quantities for trade. Using exploratory research, data were collected through Focus Group Discussions with six farmer groups, representing a total of 1255 bean farmers; and key informant interviews with extension staff. The results indicated that 94% of the farmers produced beans before identifying buyers, while only 6% participated in group marketing. Though spot-market transactions with brokers and traders provided ready cash for the farmers, formal buyers were perceived to be more reliable, but difficult to find, and operated the stringent requirements, which were a barrier to entry. Based on the study findings, sustainable production and supply of sufficient volumes for trade should entail a transformation agenda at four levels of the value chain; namely intensification of production through pure stand models with greater use of certified high yielding varieties; stable price guarantees; market-driven research and extension service; and an enabling policy and business environment in the bean value chain. Further research is needed to pilot these changes in a case control study.